Chitosan and yeast elicitor in suppressing seed-borne fungi of cucurbitaceous vegetables - Tumpa, Farzana Haque; Alam, Md Zahangir; Hossen, Kawsar; Khokon, Md Atiqur Rahman (Journal of the Bangladesh Agricultural University, 2018)
Experiments were conducted under laboratory condition to examine the efficacy of Chitosan and Yeast Elicitor to suppress the growth of seed-borne fungi of cucurbitaceous vegetables. Seeds of bottle gourd, sweet gourd, snake gourd, wax gourd and cucumber were collected from seed traders of Mymensingh districts and different seed borne fungi were isolated, purified and identified. Fourteen fungal species belonging to twelve genera consisting of Aspergillus flavus, Aspergillus niger, Botrytis cinerea, Fusarium moniliforme, Fusarium oxysporum, Phoma exigua, Rhizopus stolonifer, Macrophomina phaseolina, Penicillium spp., Curvularia lunata, Chaetomium spp., Colletotrichum spp., Cercospora spp. and Alternaria alternata were isolated and identified. Four concentrations of Chitosan and Yeast Elicitors solutions (200, 500, 1000 & 2000 ppm) including one positive control Vitavax-200 WP (0.35%) were evaluated for controlling seed-borne fungi. Among the seed treating agents Chitosan (2000 ppm) and Yeast Elicitor (2000 ppm) showed better performance in suppressing the seed-borne fungi. Chitosan (2000 ppm) showed superior performance than Yeast Elicitor (2000 ppm). Results from the present study revealed that application of elicitors as seed treatment is a potential alternative of chemical fungicide for selective vegetables. J. Bangladesh Agril. Univ. 16(2): 187-192, August 2018